(untitled) (Swiss Medical Weekly, 2019)
BACKGROUND In Switzerland, complementary medicine (CM) is officially recognised within the healthcare system and mainly practised in an integrative manner, in conjunction with conventional medicine. As in other countries, there is high demand for and use of CM with children. However, there has so far been no research into the attitude towards, training in and offer of CM among paediatricians in Switzerland. Our study addresses this gap by investigating these topics with an online survey of paediatricians in Switzerland. METHODS We conducted a national online survey using a 19-item, self-reporting questionnaire among all ordinary and junior members of the Swiss Society of Paediatrics (SSP). A comparison of the study sample with the population of all paediatricians registered with the Swiss Medical Association (FMH) allowed an assessment of the survey’s representativeness. The data analysis was performed on the overall group level as well as for predefined subgroups (e.g. sex, age, language, workplace and professional experience). RESULTS 1890 paediatricians were approached and 640, from all parts of Switzerland, responded to the survey (response rate 34%). Two thirds of respondents were female, were aged between 35 and 55 years, trained as paediatric generalist and worked in a practice. Apart from young paediatricians in training, the study sample was representative of all Swiss paediatricians. 23% had attended training in CM, most frequently in phytotherapy, homeopathy, acupuncture/traditional Chinese medicine (TCM) and anthroposophic medicine. 65% were interested in CM courses and training. 16% provide CM services to their patients and almost all paediatricians (97%) are asked by patients/parents about CM therapies. More than half of the responding paediatricians use CM for themselves or their families. 42% were willing to contribute to paediatric CM research. CONCLUSIONS In a representative sample of paediatricians in Switzerland, their personal attitude towards CM is positive, emphasised by great interest in CM training, a willingness to contribute to CM research and a high rate of paediatricians who use CM for themselves and their families. In contrast, the percentage of paediatricians offering CM is currently rather low despite strong demand for CM for children. This study provides key pointers for the future development of complementary and integrative medicine for children in Switzerland.